Menakar Al Maharah Al Lughawiyah dalam KMA 183 dengan Standar ACTFL - Dadang Firdaus; Moh. Ainin; Muashomah; Husnatul Hamidiyyah Siregar (Shaut al Arabiyyah, 2023)
This research is based on emphasizing the aspect of al maharah al lughawiyah as the main characteristic and at the same time the orientation of learning Arabic in Madrasas as stated in KMA 183 2019. In accordance with the statement that is the expectation of mastery of al maharah al lughawiyah, these aspects are described in the appendix to the KMA 183 curriculum guide. However, to see to what extent it has been contained and has the right standards, it is necessary to conduct a study by presenting language proficiency measurement standards. ACTFL is chosen because it is considered an international standard that has been tested and accommodates all aspects of language proficiency. This type of research is descriptive with a qualitative approach that describes the conformity between aspects of al maharah al lughawiyah at KMA 183 and similar standards in ACTFL. The data collected by means of documentation of KMA 183 2019 and ACTFL guidelines, then analyzed on words and narrations containing aspects of al maharah al lughawiyah. The results of the study found that the aspect of maharah kalam and kitabah, compared to the other two maharah. The form of learning activities that are directed at understanding and analyzing. According to ACTFL standards, at the Novice Law level which is equivalent to grades 1 and 2 MI, the target at KMA is higher, where according to ACTFL students at that level are still not able to use functional language.